2011
DOI: 10.1260/0144-5987.29.6.759
|View full text |Cite
|
Sign up to set email alerts
|

Influence and Sensitivity Study of Matrix Shrinkage and Swelling on Enhanced Coalbed Methane Production and CO2 Sequestration with Mixed Gas Injection

Abstract: Matrix compressibility, shrinkage and swelling can cause profound changes in porosity and permeability of coalbed during gas sorption and desorption. These factors affect the distribution of pressure, methane production and CO 2 sequestration.This paper compares the effects of cleat compression and matrix shrinkage and swelling models with the injection of different compositional gas mixtures (CO 2 and N 2 ). It shows that well performance, pressure distribution and properties of the seam are strongly affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The readers are referred to Palmer 1 and Pan and Connell 4 for a comprehensive review of these models. Coal permeability is sensitive to reservoir stress conditions and the gas sorption-induced swelling/shrinkage behavior 5 7 . This information has been extensively used in permeability models (e.g., Shiand–Durucan (SD) permeability model): where k is the permeability, k 0 is the initial permeability, C f is the cleat compressibility, σ is the effective horizontal stress, σ 0 is the initial effective horizontal stress, ε V is the volumetric swelling/shrinkage strain, ν is the Poisson’s ratio, E is the Young’s modulus, p is the pore pressure, and p 0 is the initial pore pressure 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The readers are referred to Palmer 1 and Pan and Connell 4 for a comprehensive review of these models. Coal permeability is sensitive to reservoir stress conditions and the gas sorption-induced swelling/shrinkage behavior 5 7 . This information has been extensively used in permeability models (e.g., Shiand–Durucan (SD) permeability model): where k is the permeability, k 0 is the initial permeability, C f is the cleat compressibility, σ is the effective horizontal stress, σ 0 is the initial effective horizontal stress, ε V is the volumetric swelling/shrinkage strain, ν is the Poisson’s ratio, E is the Young’s modulus, p is the pore pressure, and p 0 is the initial pore pressure 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also revealed that cleat compressibility is not constant and generally varies with pore pressure and effective stress 1 , 2 , 20 – 22 . Cleat compressibility may also change exponentially with respect to the effective stress change for certain types of coal 5 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 has the highest adsorption affinity among CO 2 , CH 4 , and N 2 , which are adsorbed gas to coal, but CO 2 injectivity is decreased by the highest reduction in cleat permeability resulting from matrix swelling (Busch and Gensterblum, 2011;Chen et al, 2009;Guo et al, 2008). Thus, mixed gas injection that CO 2 to be injected is mixed with N 2 having the lowest adsorption affinity is proposed as a way to supplement the problem of efficiency reduction in CO 2 injection (Seto et al, 2006;Zhou et al, 2011;Zhu et al, 2002). Lin et al (2008) conducted experiments of permeability alteration by injecting pure CO 2 , CH 4 , and N 2 gas, and various mixing ratios of CO 2 -N 2 mixed gas using crushed coal sample.…”
Section: Introductionmentioning
confidence: 99%
“…China has the third largest supply of coalbed methane resources in the world (Cui et al, 2008). The exploration and exploitation of coalbed methane have shown great success and several breakthroughs during the past 20 years (Cao et al, 2012a;Zhou et strata. The coal seams that have shown value in coal bed methane research and exploitation include #2, #3, #5, and #11 coal seams.…”
Section: Introductionmentioning
confidence: 99%